STUDY DESKRIPTIF KELUHAN KESEHATAN PADA MASYARAKAT DI DAERAH TERPAPAR SISA BAKAR (FLARE) INDUSTRI MINYAK BUMI - Sri Mulyani, Sri Mulyani; Deni Imam Maghfuroh, Deni Imam Maghfuroh; Uci Sulistyowati, Uci Sulistyowati (Jurnal Penelitian Kesehatan, 2013)
Complaint is born hard feelings (Because suffered something heavy, painandso on). Description research purposes on public health complaints in the area exposed to the rest of thefuel (flares) petroleum industry.The research use descriptive research design, with apopulation ofaround burning oil family ring I (450-800 m) 79 people. The sample totaled 55 people. Non probability sampling sampling with purposive sampling.Data collection wasby questionnaire, then inediting, coding, scoring, tabulating.The results indicating more than partially exposed respiratory tractas many as 31people ( 56.4% ) , gastrointestinal tract by 13 respondents ( 23.6% ) , skin by 4 respondents ( 7.3% ) and eyewere 7persons ( 12.7 % ).Conclusion son public health complaints in the areaexposed tothe rest of the fuel (flares) ove rthe petroleum industry most affected bythe respiratory tract. Recommended for health care workers more actively provide information and provide advance deducation to communities potentially affected residual fuel (flare) the petroleum industry through existing forum sand community involvementKeywords: complaints, public health, industrial petroleum.